Analisis Manfaat dan Keuntungan Marriott Bonvoy Aplikasi Terhadap Loyalitas Tamu di Sheraton Abu Dhabi Hotel and Resort - Siti Munawaroh; Yuniarto Rahmad Satato (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the benefits and advantages of the Marriott Bonvoy application on guest loyalty at Sheraton Abu Dhabi Hotel and Resort. The increasingly competitive hospitality industry requires hotels to implement innovative digital strategies to maintain and enhance guest loyalty. The main problem identified is the lack of comprehensive understanding regarding how functional, hedonic, and social benefits of the Marriott Bonvoy application influence guest loyalty in premium hotels in the Middle East region. This research employs a quantitative approach with descriptive and causal research design. Data were collected through structured online questionnaires distributed to 31 respondents who are guests of Sheraton Abu Dhabi Hotel and Resort and users of the Marriott Bonvoy application during July 4-6, 2025. The sampling technique used purposive sampling based on specific criteria. Data analysis utilized multiple linear regression with validity and reliability testing, classical assumption tests, and hypothesis testing using IBM SPSS version 29.0. The main findings reveal that all three benefit dimensions significantly influence guest loyalty, with functional benefits having the strongest impact (β = 0.385), followed by hedonic benefits (β = 0.341) and social benefits (β = 0.198). The model explains 61.8% of the variance in guest loyalty. Functional benefits such as booking convenience, mobile check-in, and mobile key features provide the greatest contribution to guest loyalty enhancement. This research concludes that the integration of digital technology through the Marriott Bonvoy application serves as an effective strategy for improving guest satisfaction and loyalty in the premium hospitality industry.